The role of face transplantation in the self-inflicted gunshot wound. Issue 12 (December 2016) - Kiwanuka, Harriet; Aycart, Mario A.; Gitlin, David F.; Devine, Elaine; Perry, Bridget J.; Win, Thet-Su; Bueno, Ericka M.; Alhefzi, Muayyad; Krezdorn, Nicco; Pomahac, Bohdan
Summary: Background: Facial self-inflicted gunshot wounds (SIGSWs) cause a devastating midfacial defect and pose a challenging problem to the reconstructive surgeon. Face transplantation (FT) has the potential for near-normal restoration in otherwise non-reconstructible defects. Two out of 7 FT recipients at Brigham and Women's Hospital (BWH) sustained SIGSWs. In this study, we illustrate the role of FT in the management of SIGSWs through an aesthetic, functional, and psychosocial examination of outcomes. Methods: We performed a retrospective analysis of individuals with SIGSWs who were screened at BWH between 2008 and 2015. We then collected data of the injuries, modes of conventional reconstruction (CR), and deficits. For the FT recipients, we critically reviewed the psychosocial screening process and post-transplantation aesthetic, functional, and psychosocial outcomes. Results: A total of six individuals post-SIGSWs were screened for FT. All of them had undergone CR, with five receiving loco-regional flaps and free tissue transfers, and one undergoing serial debridement and primary soft-tissue repair. Following CR, all suffered from residual functional and aesthetic deficits. Two underwent partial FT and one is currently undergoing FT screening. We describe the pre-transplant psychosocial screening process and the aesthetic, functional, and psychosocial outcomes of the SIGSW FT recipients. Conclusions: We examined the facial SIGSW injury, outcomes of CR, and the mechanism of FT to offer a potential solution to the shortcomings of CR. More importantly, we highlight the critical nature of the psychosocial component of the multidisciplinary evaluation given the history of mental illness and suicidal behavior in this subset of patients.